Kapitalisme Digital Dalam Media Sosial Instagram: Kritik Terhadap Perkembangan Teknologi Digital Berdasarkan Pemikiran Herbert Marcuse - Haikal Ibnu Hakim; Fitzerald Kennedy Sitorus (CV. ITTC INDONESIA, 2024)
The rapid advancement of digital technology today has the effect of a change in various sectors of society. Along with the development of technology at this time, it is accelerating and developing faster and faster, for entrepreneurs with its presence technology can be utilized to promote their products. The research uses a qualitative method through a critical approach, namely by determining the problem. the results of the study based on Herbert Marcuse's thinking, criticism of the development of digital technology in digital capitalism on Instagram social media that digital technology has become a powerful control tool in the hands of large corporations. Marcuse highlights that social media such as Instagram has become a means to manipulate and control the thoughts and behavior of individuals, by strengthening the dominance of capitalism and reducing the space for critical thinking and freedom of opinion, which shows that digital capitalism in Instagram social media not only creates economic inequality, but also threatens individual freedom and encourages conformity.